SUBCUTANEOUS TISSUE REACTIONS TO MTA, PORTLAND CEMENT AND AN EXPERIMENTAL CEMENT - Menezes, Renato; de Moraes, Fernanda Gomes; Oliveira, Rodrigo Cardoso; Letra, Ariadne; Garcia, Roberto Brandão; de Moraes, Ivaldo Gomes; Bramante, Clóvis Monteiro (Archives of Oral Research, 2005)
Objectives: To evaluate the response of rat subcutaneous tissue to MTA, Portland cement and White Portland cement plus epoxy resin. Due to similarities in composition of MTA and Portland cement, white Portland cement was mixed with epoxy resin in order to obtain a more consistent material which would be easier to work with during clinical procedures.Methodology: MTA Angelus and Type II Portland Cement were mixed with distilled water in a 3:1 powder-liquid proportion. White Portland cement was mixed with epoxy-resin in the same proportion. The materials were placed into polyethylene tubes and implanted on the back of 36 Wistar rats. Implants of empty tubes were used as control. Animals were kiled at 7, 30, and 60 days after implantation, and samples of the skin containing the tubes were removed and histologically processed. Results: At 7 days, a granulomatous tissue was observed nearby the extremity of the tube, characterized by lymphocytes, multinucleated giant cells, and abundant macrophages around a necrotic area. At 30 days, the tissue around the tube presented initial signs of repair characterized by fibrocytes and collagen fibers. A chronic inflammatory infiltrate characterized by many macrophages and some lymphocytes was also detected. At 60 days, an advanced process of repair was observed. No statistical differences were observed among the groups at 7 and 60 days (p>0,05); However some differences were seen at 30 days. More necrotic areas with granulomatous tissue and fibrosis were observed in Portland cement group when compared to the other cements (p<0,05). Lymphocytes were seen in much larger numbers in White Portland cement + epoxi resin group (p<0,05) (Kruskal-Wallis). Conclusions: The materials were not irritant to the tissues in the area, noticeably in the last periods, and did not interfere with the natural process of healing. Further studies are necessary to indicate Portland cement for clinical use, whereas MTA is already a routinely used product in endodontics.